Sectoral patterns of collaborative tie formation: Investigating geographic, cognitive, and technological dimensions - Erlend Osland Simensen; Milad Abbasiharofteh (Industrial and Corporate Change, 2022)
The literature on sectoral systems of innovation evidences the crucial importance of sectoral specificities in innovation. Also, the proximity framework enables the exploration and analysis of how various actors establish collaborative ties. However, there has not yet been much cross-fertilization between the proximity literature and sectoral systems of innovation. First, we conceptually integrate the proximity literature into sectoral studies by underlining the differences and commonalities across sectors. Second, we use a dataset of research and development (R&D) projects subsidized by the Research Council of Norway (RCN) between 2005 and 2016 to analyze the impact of geographical and cognitive proximities on collaborative tie formation in four Norwegian sectors (biotech, oil and gas, marine, and maritime). The results indicate that cognitive proximity and colocation in large cities are positively related to the creation of collaborative ties across all sectors. Yet, the joint effects of cognitive proximity and colocation in large cities vary across sectors and seem to be correlated with the complexity of sector-specific technologies.
Keywords: D85; O31; O38; 330